Contextual Factors Affecting Implementation of In-hospital Pediatric CPR Quality Improvement Interventions in a Resuscitation Collaborative. Issue 5 (26th September 2021) - Dewan, Maya; Parsons, Allison; Tegtmeyer, Ken; Wenger, Jesse; Niles, Dana; Raymond, Tia; Cheng, Adam; Skellett, Sophie; Roberts, Joan; Jani, Priti; Nadkarni, Vinay; Wolfe, Heather
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Pediatric quality improvement (QI) collaboratives are multisite clinical networks that support cooperative learning. Our goal is to identify the contextual facilitators and barriers to implementing QI resuscitation interventions within a multicenter resuscitation collaborative. Methods: A mixed-methods evaluation of the contextual facilitators and barriers to implementation of a resuscitation QI bundle. We administered a quantitative questionnaire, the Model for Understanding Success in Quality (MUSIQ), to the Pediatric Resuscitation Quality (pediRES-Q) Collaborative. Its primary goal is to optimize the care of children who experience in-hospital cardiac arrest through a resuscitation QI bundle. We also conducted semistructured phone interviews with site primary investigators adapted from the Consolidated Framework for Implementation Research qualitative interview guide. Results: All 13 actively participating US sites completed the MUSIQ questionnaire. Total MUSIQ scores ranged from 86.0 to 140.5 (median of 118.7, interquartile range 103.6–124.5). Evaluation of the QI team subsection noted a mean score of 5.5 for low implementers and 6.1 for high implementers ( P = 0.02). We conducted 8 interviews with the local QI team leadership. Contextual facilitators included a unified institutional approach to QI, a fail forward climate, leadership support, strong microculture, knowledge of other organizations, and prioritization of goals. Contextual barriers included low team tenure, no specific allocation of resources, lack of formalized QI training, and lack of support and buy-in by leaders and staff. Conclusions: Using mixed methods, we identified an association between the local QI team's strength and the successful implementation of the QI interventions.